2022
DOI: 10.1249/tjx.0000000000000208
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Implementation of Exercise Oncology Interventions: A Path Forward

Abstract: Introduction/Purpose Extensive scientific evidence supports exercise benefits after a cancer diagnosis, and the field now needs to focus on elucidating effective strategies for implementing exercise evidence-based interventions (EBIs) for cancer survivors. Methods This article brings together three implementation efforts to describe pragmatic observations and strategies when implementing exercise oncology EBIs in nonresearch settings. From these project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Implementation of this triage and referral process was accomplished using well-documented approaches suggested by a recent review of exercise oncology implementation [ 12 ] and followed the EPIS framework [ 11 ]. Buy-in from clinical leadership, including physicians and nurses, was crucial, as was informing the staff, adaptability with regard to fitting into the clinical flow, and ensuring that all medical assistant staff were comfortable with the new processes before starting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of this triage and referral process was accomplished using well-documented approaches suggested by a recent review of exercise oncology implementation [ 12 ] and followed the EPIS framework [ 11 ]. Buy-in from clinical leadership, including physicians and nurses, was crucial, as was informing the staff, adaptability with regard to fitting into the clinical flow, and ensuring that all medical assistant staff were comfortable with the new processes before starting.…”
Section: Discussionmentioning
confidence: 99%
“…Goals of the QI initiative were to evaluate whether integrating a rehabilitation navigator and applying the EXCEEDS tool would be acceptable and feasible from the perspective of patients and clinical staff, as well as to assess the extent to which this approach would improve the proportion of patients referred to appropriate exercise or rehabilitation programming. The project was guided by the EPIS framework [ 11 ] (Exploration, Preparation, Implementation, and Sustainment) and prior efforts to map exercise oncology implementation strategies onto a compendium of implementation strategies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This figure is consistent with other implementation research that suggests organisations typically employ numerous strategies [ 70 – 73 ]. To our knowledge, of studies that use the ERIC taxonomy to document implementation strategies in exercise EBI and cancer, many report fewer than ten strategies [ 42 , 74 ], with only one other study conducting comprehensive mapping [ 34 ]. Our process to identify strategies and then apply an inductive approach to develop the explanatory pathways helps address the identified gap between the number of strategies prospectively included in implementation trials and the actual number used when retrospectively identified [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…It recommends research advancing cancer rehabilitation and exercise oncology must shift focus to good health services outcomes, cost-benefit analyses, and dissemination and implementation science 12 from merely effective interventions to establish a new standard of care. Efforts are needed to identify specific strategies that would result in more robust implementation 29 optimizing triage, workflow, and referral of cancer patients. 30,31…”
Section: Researchmentioning
confidence: 99%